(3TQM BOGH GdCcds - (3CMeO Hf YeGO Hf jhSa Hf YHO GdfHj, CHh GdYHGS, TgGH GdOjf GdCbagSj Ke GdbGgQj , GHf GdpYneGO ,J (B808 (3g` s ((3CMeO Hf eMeO Hf CMeO Hf Ydi Hfi GdfLGQ s)
(3ChdgG (B:s
(3ef GdMeO ddg QHi eSHZ GdfYe hGdTcQ Ke GdKfGA GdeGfM GdfMd T GdMeO GdKfGA Ydi eSJMbg HPcQ UaGJg GdLejd hCaYGdg GdMSfI hfbjV GdMeO GdPe s
(3BNQgG (B:s
(3hHYO bhdi dQHi cd eMeO Udi GdGdg Ydi GdeNJGQ ai GdQSd GdeUWai hcd GdQSd jHdZge QHi GdSdGe SdGekG RGci GdYed JeJ GdbUjOI s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdQGHYs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B184 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B26s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs